Essentials of Accident and Emergency Medicine - Subhy Alsheikhly, Ahmed (IntechOpen, 2019)
As physicians, we have a constant passion for improving and maintaining patient's care and safety. The book is divided into three parts focusing on the essentials of general concepts, diagnosis, and management of accident and emergency medicine, as well as an academic approach to teaching in the emergency setting. The chapters selected for this book are written by an excellent group of recognized emergency surgeons and physicians from different countries and cultures facilitating a comprehensive and interesting approach to the problems of emergency treatment. We hope this book will be helpful and used worldwide by medical students, clinicians, and researchers enhancing their knowledge and advancing their objectives by a book that intends to become a reference text for research and practice within accident and emergency medicine.